Bats Without Borders: Long-Distance Movements and Implications for Disease Risk Management - Breed, Andrew C. (Ecohealth, 2010)
Fruit bats of the genus Pteropus (commonly known as flying-foxes) are the natural hosts of several recently emerged zoonotic viruses of animal and human health significance in Australia and Asia, including Hendra and Nipah viruses. Satellite telemetry was used on nine flying-foxes of three species (Pteropus alecto n = 5, P. vampyrus n = 2, and P. neohibernicus n = 2) to determine the scale and pattern of their long-distance movements and their potential to transfer these viruses between countries in the region. The animals were captured and released from six different locations in Australia, Papua New Guinea, Indonesia, and Timor-Leste. Their movements were recorded for a median of 120 (range, 47–342) days with a median total distance travelled of 393 (range, 76–3011) km per individual. Pteropus alecto individuals were observed to move between Australia and Papua New Guinea (Western Province) on four occasions, between Papua New Guinea (Western Province) and Indonesia (Papua) on ten occasions, and to traverse Torres Strait on two occasions. Pteropus vampyrus was observed to move between Timor-Leste and Indonesia (West Timor) on one occasion. These findings expand upon the current literature on the potential for transfer of zoonotic viruses by flying-foxes between countries and have implications for disease risk management and for the conservation management of flying-fox populations in Australia, New Guinea, and the Lesser Sunda Islands.